2016
DOI: 10.3389/fnagi.2016.00195
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Alteration Patterns of Brain Functional Connectivity in Progressive Mild Cognitive Impairment Patients: A Longitudinal Whole-Brain Voxel-Wise Degree Analysis

Abstract: Patients with mild cognitive impairment (MCI) are at high risk for developing Alzheimer’s disease (AD), while some of them may remain stable over decades. The underlying mechanism is still not fully understood. In this study, we aimed to explore the connectivity differences between progressive MCI (PMCI) and stable MCI (SMCI) individuals on a whole-brain scale and on a voxel-wise basis, and we also aimed to reveal the differential dynamic alteration patterns between these two disease subtypes. The resting-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Before disease transition, more severe structural or functional connectivity alterations already existed in the aMCI converters compared with non-converters (3741). From the current study, we found that the network measures from DTI data are sensitive enough to detect the topological differences even at baseline, and correlated with the disease severity evaluated by clinical scores (MMSE, MoCA, and AVLT-Immediate Recall) in aMCI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before disease transition, more severe structural or functional connectivity alterations already existed in the aMCI converters compared with non-converters (3741). From the current study, we found that the network measures from DTI data are sensitive enough to detect the topological differences even at baseline, and correlated with the disease severity evaluated by clinical scores (MMSE, MoCA, and AVLT-Immediate Recall) in aMCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning, deep learning and complex brain networks have been recently applied to the early diagnosis of neurodegenerative diseases with interesting results (3336). Specifically, functional MRI network studies have found more severe disruptions in MCI converters, which may distinguish converters from non-converters with high accuracy (3739). Structural MRI studies have also found topological differences of brain connectome between the two groups (4042).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this method, researchers found that in MCI subjects, not only functional connectivity between the left thalamus and a set of regions was decreased (Wang et al, 2012) but also functional connectivity in cortical midline structures was decreased (Ries et al, 2010). Besides, the whole-brain voxel-wise degree map measured by static functional connectivity also showed the reduced degree in the right middle occipital gyrus in the progression from MCI to AD (Deng et al, 2016). In addition, Vega et al (2016) found that elderly SCD women who reported more severe cognitive decline showed weaker negative functional connectivity within the frontal cortex and stronger positive connectivity within the right middle temporal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…See Appendix E for the differences in effect size estimates for top voxels within subregion between the proposed and naive methods. The top subregion, corresponding to the right middle temporal pole (TPOmid.R), has been reported by a connectivity analysis to be a region in which converters exhibited a decreased short-range degree of functional connectivity [ 23 ]. The other regions have already been associated with conversion to Alzheimer's disease.…”
Section: Resultsmentioning
confidence: 99%